Salmonellae and Edwardsiella tarda in Gull Feces: a Source of Contamination in Fish Processing Plants - Berg, R. W. (1972)
The incidence of Salmonella and Edwardsiella tarda in gull feces on the Oregon coast was studied to determine the role these birds may have in the contamination of fish products with these organisms. Approximately 2.1 and 0.4% of 521 fecal specimens examined were found to contain Salmonella or E. tarda, respectively.